AI Applications in Vitagen-Based Education: Expanding Opportunities and Emerging Risks in Developing Students’ Mentality - Rustamova, Nodira Rustamovna (International Journal of Mass Communication, 2025)
Vitagen-based education treats learning not only as the acquisition of disciplinary knowledge, but as the deliberate cultivation of students’ mentality – a constellation of metacognitive, self-regulatory, motivational, and socio-emotional dispositions that shape how individuals relate to themselves, others, and a rapidly changing world. This article explores how artificial intelligence (AI) can both strengthen and destabilise this project. First, it reconstructs the theoretical foundations of vitagen-based education and clarifies the notion of mentality in relation to agency, reflection, and lifelong learning. It then maps four major clusters of AI applications – personalisation and adaptive pathways, intelligent mentoring and feedback, assessment and data-informed insights, and learning analytics for mentality development – showing how these tools can scaffold reflection, support growth mindset, and extend socio-emotional learning when carefully designed. At the same time, the article identifies four interlocking domains of risk: privacy and surveillance; bias, fairness, and inclusivity; dependency and erosion of critical thinking; and mental health and well-being. Drawing on international cases and longitudinal studies, the analysis distils pedagogical and policy implications for curriculum design, teacher professional development, and multi-level governance of AI in education. Finally, it outlines a research agenda for AI-enhanced vitagen education, arguing for ethically grounded, mixed-methods and cross-disciplinary inquiry. The article contends that AI will not automatically elevate vitagen-based education, but, under well-governed conditions, can become a powerful – though never neutral – partner in developing students’ mentality.